EFEKTIVITAS PENDIDIKAN KESEHATAN SECARA INDIVIDUAL DENGAN MENGGUNAKAN MEDIA FLIPBOOK TERHADAP SELF-EFFICACY PASIEN HIPERTENSI DALAM MENGONTROL DIET - Ramadhani, Nurpatri; Utami, Gamya Tri; Ernawaty, Juniar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Health education is one of the efforts to influence the community by providing information and giving awareness to adopt and behave healthy which can improve their health status. The health education is given by using flipbook media. This study aimed to determine the effectiveness of individual health education by using flipbook media on self-efficacy of hypertensive patients in controlling diet. The method used in this study was a quasy experiment with a nonrandomized pretest posttest control group design. Purposive sampling technique was applied to determine the sample consisted of 34 respondents divided into 2 groups; experiment and control group. The instrument used was a questionnaire about the self-efficacy of hypertensive patients in controlling the diet that had been tested for validity (0.464-0.667) and reliability (0.898). The analysis utilized were univariate and bivariate analysis using t dependent and independent t test. The results showed there was an influence of individual health education by using flipbook media on self-efficacy of hypertensive patients in controlling diet with p value (0,000) < Î± (0,05). The results of this study recommend that health workers should provide health education individually because each person has different health problems and use flipbook media to improve self-efficacy of hypertensive patients in controlling diet. Â Keywords : Flipbook, health education, hypertension diet, self-efficacy